PSMA Accumulation in Benign Pleural Thickening - Kevser Oksuzoglu; Ilknur Alsan Cetin; Feyza Sen; Tunc Ones; Reza Maleki; Halil Turgut Turoglu; Tanju Yusuf Erdil (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2016)
Prostate-specific membrane antigen (PSMA) is a specific type II membrane glycoprotein. We present the case of a 72-year-old man with newly diagnosed prostate cancer who had a 68 Ga-PSMA PET/CT scan for staging.68 Ga-PSMA PET/CT images showed moderate uptake in the right hemithorax,corresponding to pleural thickening seen on the CT images. Histopathologic examination revealed the diagnosis of chronic inflammation. It is important to keep in mind other alternative diagnoses such as chronic inflammation when 68 Ga-PSMA PET/CT identifies uptake at an atypical site.